Seed and petal yield of non-spiny cultivars of safflower (Carthamus tinctorius L.) under rainfed conditions: Seed and petal yield of non-spiny cultivars of safflower (Carthamus tinctorius L.) under rainfed conditions - P PADMAVATHI,; PRADUMAN YADAV, (Journal of Oilseeds Research, 2020)
Eight non-spiny cultivars were evaluated under rainfed conditions during the post rainy season of 2012-13 for their seed and petal yield in comparison to two spiny cultivars. Spiny cultivars gave significantly greater yields (1515 kg/ha) compared to non-spiny cultivars (911 kg/ha). Among the non-spiny cultivars NARI-NH-1 and NARI-6 (1175 kg/ha) were significantly superior over other non-spiny cultivars (823 kg/ha).